2020
DOI: 10.1093/brain/awz393
|View full text |Cite
|
Sign up to set email alerts
|

Microglia and macrophage phenotypes in intracerebral haemorrhage injury: therapeutic opportunities

Abstract: The prognosis of intracerebral haemorrhage continues to be devastating despite much research into this condition. A prominent feature of intracerebral haemorrhage is neuroinflammation, particularly the excessive representation of pro-inflammatory CNS-intrinsic microglia and monocyte-derived macrophages that infiltrate from the circulation. The pro-inflammatory microglia/macrophages produce injury-enhancing factors, including inflammatory cytokines, matrix metalloproteinases and reactive oxygen species. Convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 144 publications
5
102
0
Order By: Relevance
“…As shown in Figures 7A-D, the expression of both IL-1β and TNF-α was decreased over time in two groups, and the ICH + Hydrogel group showed significantly lower of both two pro-inflammatory cytokines than that in the ICH + Vehicle group (P < 0.001), indicating that the hydrogel is capable of anti-inflammation in the ICH mouse model. In general, proinflammatory cytokines are thought to be produced mainly by activated M1 microglia/macrophages in the brain (Bai et al, 2020), Our results have shown that the hydrogel injection can inhibit the M1 phenotype, which might explain the decreased expression of the IL-1β and TNF-α .…”
Section: Gelatin Hydrogel Injection Reduced the Release Of Il-1β And mentioning
confidence: 58%
See 1 more Smart Citation
“…As shown in Figures 7A-D, the expression of both IL-1β and TNF-α was decreased over time in two groups, and the ICH + Hydrogel group showed significantly lower of both two pro-inflammatory cytokines than that in the ICH + Vehicle group (P < 0.001), indicating that the hydrogel is capable of anti-inflammation in the ICH mouse model. In general, proinflammatory cytokines are thought to be produced mainly by activated M1 microglia/macrophages in the brain (Bai et al, 2020), Our results have shown that the hydrogel injection can inhibit the M1 phenotype, which might explain the decreased expression of the IL-1β and TNF-α .…”
Section: Gelatin Hydrogel Injection Reduced the Release Of Il-1β And mentioning
confidence: 58%
“…For brain implantation, like other implants, the immune response which partly depending on the characteristics of the implants such as biocompatibility significantly influences the interaction between the hydrogel and the surrounding host tissues (Tsui et al, 2019;Wissing et al, 2019). As a key innate immune cell in the brain, microglia is the most important defense against exogenous threats, where activated microglia/macrophages develop into two subtypes: pro-inflammatory microglia (M1, classically activated) and anti-inflammatory microglia (M2, alternatively activated) (Xiong et al, 2016), the polarization of which plays a crucial role in promoting the recovery of brain injury and nerve (Bai et al, 2020). Nevertheless, how to modulate the immune response and neuroinflammation through the implanted biomaterials such as hydrogel remains a great challenge to date.…”
Section: Introductionmentioning
confidence: 99%
“…It is documented that microglia will secrete a large amount of proinflammatory cytokines when stimulated [26]. Previous studies have demonstrated that microglia can be activated by ICH which contributes to the secretion of proinflammatory cytokines during the occurrence of disease [27]. Recently, miR-340-5p was determined to be involved in the anti-inflammatory effects of dexmedetomidine in the nervous system, and overexpression of miR-340-5p enhanced the protective effect of dexmedetomidine in LPS-stimulated BV-2 cells [23].…”
Section: Pdcd4 Was a Direct Target Gene Of Mir-340-5pmentioning
confidence: 99%
“…1,2 Neuroinflammation in ischemic brain results from the activation of microglia, the brain-resident macrophages, and from blood-borne macrophages that infiltrate from the circulation. [3][4][5] Microglia rapidly develop a pro-inflammatory phenotype in response to acute stroke injury; meanwhile, activation of microglia also present reparative and anti-inflammatory roles through a regulatory/ homeostatic phenotype, which facilitates recovery. 3,[6][7][8][9] Neuroinflammation accompanies these changes in the phenotypes of the microglia/macrophages after ischemic stroke, with one phenotype predominating over another in a time-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Microglia rapidly develop a pro-inflammatory phenotype in response to acute stroke injury; meanwhile, activation of microglia also present reparative and anti-inflammatory roles through a regulatory/ homeostatic phenotype, which facilitates recovery. 3,[6][7][8][9] Neuroinflammation accompanies these changes in the phenotypes of the microglia/macrophages after ischemic stroke, with one phenotype predominating over another in a time-dependent manner. 7,10,11 Dynamic analysis by ourselves and others have demonstrated that the location of the active microglia/macrophages with respect to the infarct in ischemic brain at different stages is a critical feature of these immune phenotypes.…”
Section: Introductionmentioning
confidence: 99%